Street in front of Northern Commercial Co. building, Dawson, n.d. - Nowell, Frank H., 1864-1950 (1894)
Caption on image: 6267 On verso of image: Dawson City, YT To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number